Selection Strategy of Jaw Tracking in VMAT Planning for Lung SBRT - Sun, Wuji; Shi, Yinghua; Li, Yu; Ge, Chao; Yang, Xu; Xia, Wenming; Chen, Kunzhi; Wang, Libo; Dong, Lihua; Wang, Huidong (Frontiers in Oncology, 2022)
Purpose: This study aimed to investigate the dosimetric effect and the delivery reliability of jaw tracking (JT) with increasing PTV volume for lung stereotactic body radiation therapy (SBRT) plans. A threshold of PTV volume was proposed as a selection criterion between JT and fixed-jaw (FJ) techniques. Methods: A total of 28 patients with early-stage non-small-cell lung cancer were retrospectively included. The planning target volumes (PTVs) ranged from 4.88 cc to 68.74 cc, prescribed with 48 Gy in four fractions. Three-partial-arc VMAT plans with FJ and with JT were created for each patient, with the same optimization objectives. These two sets of plans were compared using metrics, including conformity index (CI), V50%, R50%, D2cm, dose-volume parameters of organs at risk, and monitor units (MUs). The ratio of small sub-fields (< 3 cm in either dimension), %SS, was acquired as a surrogate for the small-field uncertainty. Statistical analyses were performed to evaluate the correlation between the differences in these parameters and the PTV volume. Results: The V50%, R50%, D2cm, and V20Gy, D1500cc, and D1000cc of the lung showed a statistically significant improvement in JT plans as opposed to FJ plans, while the number of MU in JT plans were higher by an average of 1.9%. Between FJ and JT plans, the PTV volume was strongly correlated with the differences in V50%, moderately correlated with those in V20Gy of the lung, and weakly correlated with those in D2cm and D1500cc of the lung. By using JT, %SS was found to be negatively correlated with the PTV volume, and the PTV volume should be at least approximately 12.5 cc for an expected %SS < 50%, which was 15 cc for a %SS < 20% and 20 cc for a %SS < 5%. Conclusions: Considering the dosimetric differences and small-field uncertainties, JT could be selected using a PTV volume threshold, such as 12.5, 15, or 20 cc, on the basis of the demand of delivery reliability for lung SBRT.